Pengaruh Pemanfaatan Media Tutorial Berbentuk Film Motion Pictures Terhadap Motivasi Belajar Siswa - Nurul Perdana Putri; Hadi Gunawan Sakti (UNDIKMA, 2021)
The purpose of this study was to determine the effect of using tutorial media in the form of motion pictures on student motivation in class X ICT subjects at MA Darul Qur'an Wal Hadits. This research method using experiment. The population in this study were all students of class X at MA Darul Qur'an Wal Hadits 101 with a sample of 30 students. Data collection techniques in this study used a documentation questionnaire, observation and interviews. The data analysis technique used the t-test. From the research results obtained t-test of 3.481 with a significance level of 5% and d.b N-1 = (30-1 = 29) of 2.045. This shows that Ho is rejected and Ha is accepted, so it is concluded that there is an effect of the use of tutuorial media in the form of motion pictures on students' learning motivation in the X grade typology subject at MA Darul Qur'an Wal Hadits.